Pemanfaatan Ekstrak Ubi Ungu sebagai Pewarna Merah pada Soft Candy dan Stabilitasnya - Putu Timur Ina; Gusti Ayu Kadek Diah Puspawati; Gusti Ayu Ekawati; Gusti Putu Ganda Putra (agriTECH, 2019)
This study aimed to determine the purple sweet potato pigment extract concentration in soft candy formulation and its stability during storage. The research was conducted in two steps i.e. the addition of purple sweet potato pigment extract concentration in soft candy and of soft candy’s red pigment stability during storage. Firstly, the soft candy formulation was added with the red pigment of purple sweet potato extract in various concentrations, i.e. control (0% extract); 0.25% concentration of the pigment extract; 0.50%; 0.75%; and 1%. Secondly, the stability examination of pigment extract in soft candy was carried out at various storage temperatures: at refrigerator temperature (4 °C); at room temperature (27 ℃); and at 35 °C within the observation period of every 2 days for 14 days. The results showed that soft candy with the purple sweet potato red pigment extract addition of 0.75% concentration gave the highest value on panelists’ acceptance in terms of color, odor, texture, taste and overall acceptance as follows: 6.08 (like); 4.02 (neutral); 5.58 (like); 5.46 (rather like); and 5.92 (like), respectively, with the following levels of anthocyanin, total phenolic and antioxidant activity: 12,74±0,06 mg/100 g; 0,73±0,02 g/100 g and 0,76±0,02 g AAE/100 g, respectively. Stability of soft candy’s red pigment extract during storage at a temperature of 35 °C for 14 days showed a decline in the value of a* (redness), but an increase in the value of b* (yellowness) and the value of L (brightness), as a significant indicator of the purple sweet potato red pigment extract color change on soft candy, meanwhile at refrigerator (4 ℃) and room temperatures (27 ℃) after 14 days observation has not shown the loss or a significant reduction of red pigment color.